2012
DOI: 10.1111/j.1756-185x.2012.01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of osteoporosis and BMD below the expected range for age among South Korean women with rheumatoid arthritis

Abstract: The prevalence of osteoporosis in the RA patients was 1.9 times higher than in healthy subjects. Glucocorticoid use was a risk factor for generalized bone loss in female RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 23 publications
(42 reference statements)
2
45
1
3
Order By: Relevance
“…In addition, the RA patients with hip fractures had significantly higher 6-month and 1-year mortality rates compared with RA patients without hip fractures (Table 3). Because there was a high prevalence of corticosteroid [18] or immunosuppressive agent [19,20] use among patients in the RA group, we further investigated the incidence of infection-related complications after hip fracture in both groups after matching for age and gender. The incidence of septicemia, pneumonia, and osteomyelitis was higher in the RA group than the control group (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the RA patients with hip fractures had significantly higher 6-month and 1-year mortality rates compared with RA patients without hip fractures (Table 3). Because there was a high prevalence of corticosteroid [18] or immunosuppressive agent [19,20] use among patients in the RA group, we further investigated the incidence of infection-related complications after hip fracture in both groups after matching for age and gender. The incidence of septicemia, pneumonia, and osteomyelitis was higher in the RA group than the control group (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Glucocorticoid-induced osteoporosis (GIOP) in RA patients has become a wellknown phenomenon and increases fracture risk [26]. More than 50 % (51.6 %) of RA patients were co-prescribing oral steroids [17] which may lead to the high prevalence of osteoporosis and contribute to the high incidence of hip fracture among RA patients [4,18,27]. Furthermore, van Staa et al suggested that 47 % of all hip and 72 % of all vertebral fractures that occurred can be attributed to oral corticosteroid use [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Our findings were consistent with other studies reported that RA was associated with OP, a previous study has shown that there is a higher prevalence of OP in a group of Korean female RA patients (22.1%) compared with the healthy control group (11.4%). 17 Similarly, cohort study of 394 female patients with RA compared to control also revealed doubled preva-lence of OP. 18 A study focusing on young patients with RA.…”
Section: Resultsmentioning
confidence: 95%
“…Of course, study of healthy women before and after menopause might find similar numbers. However, there is clearly excess osteoporosis among RA women compared to controls with post-menopausal status an important predictor 74 . Excess bone loss seen in RA occurs early in the disease 75 .…”
Section: Rheumatoid Arthritismentioning
confidence: 99%